Regional cooperation and integration in Asia and the Pacific implementation of the operational plan for regional cooperation and integration, 2016-2020 corporate progress report 2017. (Metro Manila, Philippines Asian Development Bank, 2017)
Regional cooperation and integration (RCI) has become a valuable means for attaining national development goals. This corporate report takes stock of ADBs RCI operations, focusing on 2016, by reviewing progress made and identifying areas for improvement. It complements ADBs existing RCI reports by focusing on RCI progress aligned with the three operational directions (connectivity, competitiveness, and regional public goods and collective action) and the three approaches (nascent RCI, nonsovereign RCI, and intersubregional RCI) to RCI operational quality. This corporate report pools together and offers a one-stop source of information on RCI operations for both internal and external stakeholders.
Keywords: Pacific Area -- Economic integration; Electronic books